Metagenomic Sequencing and Histology on a Chronic Wound Identified Epstein-Barr Virus-Associated Lymphoma. (July 2022) - Yang, Wan-Ting; Chiang, I; Tseng, Chien-Hao; Cheng, Chun; Lin, Jyun-Hong; Liu, Po-Yu; Huang, Yao-Ting
Accurate diagnosis of chronic, non-healing wounds is challenging and time-consuming because it can be caused by a variety of etiologies. This brief report presents an unusual case of a chronic wound lasting for 10 months investigated by deep metagenomic sequencing. Epstein-Barr virus (EBV) was identified in the wound and subsequently validated by in situ hybridization. Histopathologic examination eventually revealed that the non-healing wound was due to an EBV-associated NK/T cell lymphoma. By identifying mutations across the viral genome, the virus was classified as Type I EBV and clustered with others of geographic proximity. Our results suggest that metagenomic shotgun sequencing can not only rapidly and accurately identify the presence of underlying pathogens but also provide strain-level resolution for the surveillance of viral epidemiology.